Analisis Manajemen Strategi Baitul Maal Pupuk KujangAnalisis Manajemen Strategi Baitul Maal Pupuk Kujang - Ratna Ayu; Angga Sanita Putra (Journal on Education, 2023)
Zakat is one way to help people's economic recovery after the Covid-19 pandemic, especially people who are classified as less fortunate. Zakat management is expected to be ideal, therefore a good strategy is needed that reflects amil zakat institutions with scientific and technical capabilities to achieve their goals. This study aims to determine the management strategy in the management of zakat at Baitul Maal Pupuk Kujang. The research method used is a qualitative method with an analytical tool, namely SWOT analysis (Strength, Weaknesses, Opportunities, Threats). From the results of the organizational profile analysis and environmental analysis it is known that the strengths, weakness, opportunity, and threats. Baitul Maal Pupuk Kujang. Baitul Maal Pupuk Kujang has weaknesses such as the coverage of Muzakki is still too narrow, many people still don't know Baitul Maal Pupuk Kujang, there is no systematic and digitally connected zakat management and human resources are still minimal so management and distribution are still not optimal. By maximizing strengths from the internal side and opportunities from the external side as well as utilizing the large potential of zakat, Baitul Maal Pupuk Kujang can become an institution that the community can trust.